2002
DOI: 10.1002/14651858.cd001141
|View full text |Cite
|
Sign up to set email alerts
|

Support for breastfeeding mothers

Abstract: The provision of extra support by professionals with special skills in breastfeeding appears to result in more mothers breastfeeding their babies until two months of age, and more mothers breastfeeding their babies exclusively to two months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 0 publications
5
90
0
1
Order By: Relevance
“…Support with breastfeeding problems and promotion of exclusive breastfeeding through existing primary health care services seems to be feasible and effective in increasing the length of time that women exclusively breastfeed. 15,31 These studies also demonstrate the importance of lay support and community-based efforts in promoting exclusive breastfeeding.…”
Section: Comparison With Other Studiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Support with breastfeeding problems and promotion of exclusive breastfeeding through existing primary health care services seems to be feasible and effective in increasing the length of time that women exclusively breastfeed. 15,31 These studies also demonstrate the importance of lay support and community-based efforts in promoting exclusive breastfeeding.…”
Section: Comparison With Other Studiesmentioning
confidence: 78%
“…[15][16][17][18] Most randomized trials of such interventions, however, have had time-intensive interventions that occurred as adjuncts to routine preventive visits rather than within them. Little information is available on whether pediatricians or other clinicians can affect breastfeeding rates via specific advice or practices during routine preventive visits.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…In Mangochi, Malawi, Vaahtera et al (2001) reported a positive association between maternal education and prolonged breastfeeding. In a Bolivian study, education was the only significant factor associated with knowledge about the advantages of breastfeeding , and efforts to promote breastfeeding have been found to be effective in increasing short-term exclusive breastfeeding (Sikorski et al, 2002). The economic circumstances of many of these young mothers was poor, with some experiencing extreme poverty.…”
Section: Mean W/a Z-scorementioning
confidence: 99%
“…The effect of ante/postpartum breastfeeding education on increasing exclusive breastfeeding rates has been shown by several studies in literature (12,19,20,21). In the common report prepared by the WHO and UNICEF on "Protecting, Promoting and Supporting Breastfeeding", attention is drawn to the importance of healthcare education and practices in adopting and lengthening breastfeeding, and the midwives who carry out mother-child healthcare services are assigned the duty of furnishing mothers with appropriate information on, and supporting them in, breastfeeding (22).…”
Section: Discussionmentioning
confidence: 99%